Demographic infuences on green infrastructure awareness among urban practitioners: evidence from Yemen - Asmawi, Zainora; Ahmed Bagazi, Omer Ali; Dewan, Ashraf (Springer Nature, 2025)
Green infrastructure (GI) is a term that focuses on achieving sustainable development across various dimensions, including social, economic, and environmental aspects. It serves as a platform to strike a balance between preserving the environment and developing urban areas, while also delivering environmental, social, and economic benefits to create a favorable environment for urban residents. However, many countries, particularly developing ones like Yemen, face challenges in planning and implementing GI effectively. As professionals play a key role in this process, it is essential to integrate GI elements into city planning and development. Understanding the level of awareness among professionals, including demographic information, is crucial. This study examines the awareness of GI concepts among practitioners based on factors such as gender, age, type of agency, experience, and education. Through data analysis of a primary survey conducted in Yemen, the study utilised descriptive statistics and ANOVA tests to identify significant relationships between these demographic factors and GI awareness. The results reveal that female practitioners have a higher level of awareness compared to male practitioners, with a statistically significant correlation. Additionally, education level significantly influences GI awareness, with postgraduate practitioners showing the highest awareness. However, age, type of agency, and experience do not demonstrate statistically significant differences in GI awareness. The study highlights the importance of targeted awareness initiatives, especially for less-educated practitioners, to enhance GI knowledge and implementation